A Preliminary Study on Musculoskeletal Disorders (MSDs) Among Office Workers - Mohd Irsyad Bin Marhan; Nurrul Hafeezah Binti Sahak (Progress in Engineering Application and Technology, 2023)
Working in the office usually involved in a repetitive movement, prolonged sitting, and many other activities that eventually can cause musculoskeletal disorder or MSDs. It is important to identify the effect of MSDs towards workers and ensure that the workers who spent most of the time in the office environment is safe form MSDs. The purpose of this study is to determine the prevalence of MSDs on the most common body parts among 55 MRT Corp employees in Standard and Compliance Division, measure the level of ergonomic awareness among those employees and subsequently, recommend counter measures to reduce the effect of MSDs among those employees. The method used in this study was questionnaire which consist of 6 sections which is section A for socio demographic, section B for work information, section C for social lifestyle, section D for awareness, section E for ergonomic practices and section F for Cornell Musculoskeletal discomfort Questionnaire (CMDQ). Statistical Package for the Social Science (SPSS) was used to analyze the data. The result of this study found that the most common body part to experience an MSDs was the neck with 78.1% experienced it at least once in the previous week. It also stated that the awareness level of ergonomics among those employees was high. It was recommended that MRT Corp should focused on creating extensive programs for workplace health promotion that provides workers guidance on managing a healthy lifestyle as well as advice and as well as training on workstation ergonomics and work organization to reduce the effect of MSDs among its employees.